A Comparative CFD Study on Simulating Flameless Oxy-Fuel Combustion in a Pilot-Scale Furnace. (16th October 2016) - Ghadamgahi, Mersedeh; Ölund, Patrik; Ekman, Tomas; Andersson, Nils; Jönsson, Pär
Abstract : The current study presents a method to model the flameless oxy-fuel system, with a comparative approach, as well as validation of the predictions. The validation has been done by comparing the predicted results with previously published experimental results from a 200 kW pilot furnace. A suction pyrometer has been used to measure the local temperature and concentrations of CO, CO2, and O2 at 24 different locations. A three-dimensional CFD model was developed and the validity of using different submodels describing turbulence and chemical reactions was evaluated. The standard k - ε model was compared with the realizable k - ε model for turbulence, while Probability Density Function (PDF) with either chemical equilibrium or the Steady Laminar Flamelet Model (SLFM) was evaluated for combustion. Radiation was described using a Discrete Ordinates Model (DOM) with weighted-sum-of-grey-gases model (WSGGM). The smallest deviation between predictions and experiments for temperature (1.2%) was found using the realizable k - ε model and the SLFM. This improvement affects the prediction of gaseous species as well since the deviation between predictions and experiments for CO2 volume percentages decreased from 6% to 1.5%. This provides a recommendation for model selections in further studies on flameless oxy-fuel combustion.